Struggling to find our way : rural educators' experiences working with and caring for Latinx students - Oudghiri, Stephanie (Research for social justice., 2022)
"Rural communities across the United States are experiencing a rapid increase in the number of immigrant students. While the number of culturally and linguistically diverse students continues to grow within midwestern states, the demographics of teachers remain white, female, and monolingual. Often teachers have little to no training working with students and their families whose backgrounds differ from their own. Thus, there is a great urgency for teachers to develop culturally competent teaching practices that address the needs of all students. The purpose of this year-long, school-based narrative inquiry was to examine the beliefs, attitudes, and practices of rural educators as they described their work with Latinx immigrant, elementary students, negotiated the "space" between a professional and personal identity and demonstrated an ethic of care. This inquiry is arranged into "livings, tellings, retellings, and relivings" (Clandinin & Connelly, 2000, p. 70) and serves to shed light on the entwined lived experiences of myself, my participants, and the community in which we reside. Grounded in Noddings (1984; 2012) work on authentic caring and Valenzuela's (1999) concept of culture and caring relations for Latinx students, Swanson's middle range theory of care (1991, 1993) which served as the conceptual framework that illuminated how my participants discussed working with and caring for their Latinx immigrant students. In 'Struggling to Find Our Way:' Rural Educators' Experiences Working with And Caring for Latinx Immigrant Students, Stephanie Oudghiri's one-year school-based narrative inquiry is a carefully crafted balance of creativity and rigor with the right notes to engage the reader, challenge them to think, wonder at what they can do, and imagine possibilities for a more socially just education system. In this book, Oudghiri examines the beliefs, attitudes, and practices of two white teachers and one Hispanic paraprofessional working with and caring for immigrant students in a rural Indiana community. Due to the sensitive nature of this inquiry, which focuses on teachers' relationships with vulnerable populations (immigrant and undocumented), Oudghiri's book serves as a model for active engagement by creating a strong sense of place, a strong sense of who these teachers and students are, and a strong sense of being in the midst of community and school life. What is unique and compelling about Oudghiri's writing, is her focus on stories of the teachers working in her school site, and the children in their classrooms. She provides strong evidence using a compassionate lens and the art of storytelling to illuminate lives in the school"--